Preparation method of super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel
By optimizing the electric arc furnace-AOD/VOD-LF process flow and elements, ultra-large-sized high-temperature resistant concentrated sulfuric acid austenitic stainless steel was prepared, solving the corrosion and leakage problems and complex construction issues of sulfuric acid production equipment, and realizing an efficient and low-cost material solution.
Patent Information
- Application Number
- CN202310745397.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-21
- Publication Date
- 2025-11-07
- Estimated Expiration
- 2043-06-21
AI Technical Summary
In existing technologies, the drying towers and absorption towers of sulfuric acid production equipment suffer from high corrosion and leakage rates, complex construction, and high costs. Traditional materials cannot effectively meet the needs of ultra-large size, high temperature and high concentration sulfuric acid.
By employing an electric arc furnace-AOD/VOD-LF process and precisely controlling oxygen blowing parameters and slag composition, ultra-large-sized high-temperature concentrated sulfuric acid resistant austenitic stainless steel is prepared. By combining side and top oxygen blowing methods and optimizing the content of elements such as chromium, nickel, and silicon, stainless steel with excellent resistance to sulfuric acid corrosion is formed.
It has enabled the efficient preparation of ultra-large stainless steel, reduced chromium burn-off, improved the yield and corrosion resistance of the material, reduced construction costs, avoided potential welding quality problems, and adapted to the production process requirements of sulfuric acid at different temperatures and concentrations.
Smart Images

Figure CN117026058B_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to a preparation method of an ultra-large-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel and belongs to the technical field of austenitic stainless steel. BACKGROUND
[0002] Sulfuric acid, as an important industrial raw material, is also known as the mother of industry, and can be used to manufacture fertilizers, drugs, explosives, pigments, detergents, storage batteries and the like, and is widely applied to the industries of purifying petroleum, metal smelting and dyes, and can also be used as a chemical reagent and a dehydrating agent and a sulfonating agent in organic synthesis.
[0003] In the production process of sulfuric acid, the drying tower and the absorption tower generally adopt a structure that a steel shell is lined with acid-resistant ceramic tiles. Many years of production practice shows that this structure has many defects: firstly, the tower body lined with acid-resistant ceramic tiles has a high leakage rate, and safety accidents such as expansion and cracking of the steel shell are prone to occur; secondly, the tower body lined with ceramic tiles is very heavy, and the construction is complex, the manufacturing period is long, and the operation and maintenance costs are high. In the conveying components of sulfuric acid, the traditional corrosion-resistant materials usually adopt low-chromium cast iron, high-silicon cast iron, polytetrafluoroethylene, sulfuric acid-resistant stainless steel, nickel-based alloy and the like, but these materials each have a use range, or the cost is too high, and the industry demand cannot be effectively met.
[0004] According to incomplete statistics, 30% to 40% of the drying towers and the absorption towers of sulfuric acid plants in China have occurred tower body corrosion leakage accidents, and the work difficulty of leakage treatment after the tower body corrosion leakage is extremely great, and the treatment is often a temporary solution rather than a permanent solution. For this reason, foreign equipment and steel industry leading enterprises begin to jointly research and develop special stainless steel to replace the steel shell lined with acid-resistant ceramic tiles to manufacture the drying and absorption towers, increase the safety of the equipment and reduce the production operation and maintenance costs. For example, foreign companies have developed Zecor (similar to ASTM S38815), Saramet 35, sandvik SX (similar to ASTM S32615) and the like, but due to the reasons of processing technology, use performance, cost and the like, the special stainless steel cannot be widely applied in China. In recent years, individual domestic chemical enterprises begin to import special sulfuric acid-resistant stainless steel to manufacture the shell-and-tube concentrated sulfuric acid cooler and the acid distributor of the drying and absorption towers, but most of the drying and absorption towers are still manufactured by using the traditional steel shell lined with acid-resistant ceramic tiles; in recent years, some special high-temperature-resistant concentrated sulfuric acid steel plates are used in China, but the size of the steel plates is very small (width ≤1000 mm, length ≤2500 mm, thickness ≥6 mm), so that the welding workload is very large in the equipment manufacturing process, the construction cost is high, and there are serious welding quality hidden dangers.
[0005] Therefore, the sulfuric acid (especially high-temperature high-concentration sulfuric acid) production industry and the engineering construction industry requiring the use of sulfuric acid urgently need a new material with ultra-large size, excellent sulfuric acid corrosion resistance, process processing performance and reasonable cost. SUMMARY
[0006] The present application solves the above problems, and provides a preparation method of an ultra-large-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel. The ultra-large size refers to a width of ≥1600 mm, a length of ≥6000 mm, and a thickness of ≥6 mm.
[0007] The technical scheme for solving the above problems is as follows:
[0008] A preparation method of an ultra-large-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel, comprising the following steps:
[0009] 1) batching: according to the chemical composition of the austenitic stainless steel and the burning loss, raw materials are prepared, the raw materials are melted into molten steel, 28-35 kg / t of slag forming agent is added for primary refining, the oxidized metal in the molten steel is reduced by a reducing agent, and the Cr content in the molten steel is adjusted to be higher than the lower limit of the target value specified for the steel grade; when the temperature of the molten steel reaches 1625-1650℃, the molten steel is discharged;
[0010] 2) oxygen blowing decarburization: the molten steel is poured into an argon-oxygen refining furnace or a vacuum decarburization refining furnace (AOD / VOD), slag is first drawn, then the alloy raw material to be added is calculated according to the composition of the poured steel, the temperature of the molten steel is maintained above 1600℃, then refining is performed, oxygen blowing decarburization is performed when the initial carbon content is 1.0±0.2%, 28-35 kg / t of slag forming agent is added for slagging, and the temperature is controlled to reach 1730℃, and when the carbon is lower than 0.018%, the next step is entered;
[0011] 3) reduction: 10-15 kg / t of ferrosilicon alloy is added to the molten steel for pre-reduction, after the chromium oxide in the slag is completely reduced, all the pre-reduction slag is removed, and the silicon element reaches the target value; the slag forming agent is added again, 1.5-2.0 kg / T of strong deoxidizer aluminum is added, and deep deoxidization and desulfurization are performed;
[0012] 4) tapping: the molten steel after completing deoxidization is analyzed for chemical composition, and if necessary, Ni, Cr, Mo and other alloy elements are added for final composition fine tuning, argon is blown in for stirring, and when the temperature is 1590-1630℃, the molten steel is tapped into an LF ladle;
[0013] 5) ladle refining: the slag is polarized by an electrode, and the temperature is raised, the temperature is adjusted to the casting temperature, argon is bottom blown, and the non-metallic inclusions in the molten steel are removed by using dispersed argon bubbles;
[0014] 6) casting: the molten steel in the LF ladle is cast into an ingot by using the bottom pouring method, the ingot is slowly cooled and then demolded, the cooling speed is ≤100℃ / h, the cooling speed is prevented from being too large to cause cracking due to excessive internal stress of the ingot; the shape of the ingot is a tapered square ingot, the size of the large end of the ingot is between 600-700 mm, and the size of the small end of the ingot is between 500-600 mm;
[0015] 7) Open up: after the surface treatment of the ingot through forging equipment open up; ingot heating temperature 1140-1200 ℃, final rolling or final forging temperature is ensured above 950 ℃; open up fire time is divided into three fires, the first fire ingot is roughed to 1300-1400 mm, the second fire the slab is transversely expanded, the thickness reaches 300 mm, the width reaches 1450 mm, the third fire the slab is longitudinally elongated, the final steel blank size reaches width > 1500 mm, thickness > 180 mm, length > 2200 mm;
[0016] 8) Hot rolling: first time hot rolling, the blank heating temperature is 1150-1190 ℃, the final rolling temperature is ensured above 950 ℃; the first time hot rolling size width is greater than 1550 mm, thickness is greater than 28 mm; second time hot rolling, the blank heating temperature is 1150-1170 ℃, the final rolling temperature is ensured above 960 ℃; the second time hot rolling size width is greater than 1650 mm, thickness is between 6.0-12.0 mm, length > 6500 mm;
[0017] 9) Solid solution: solid solution temperature is 1060-1100 ℃, holding time is 15-20 min.
[0018] The present application adopts the process flow of electric arc furnace-AOD / VOD-LF, specifically, in the decarburization process, the balance relationship of chromium-carbon-temperature in stainless steel smelting is fully considered, the oxygen blowing parameters are accurately controlled, the reasonable oxygen-argon ratio or oxygen-nitrogen ratio control is matched, the rapid temperature rise and high temperature maintenance of the duration are ensured, the carbon is preferentially oxidized, the oxygen supply intensity is improved, the oxygen blowing time is obviously shortened, the chromium burning loss is reduced, and the end point carbon content is reduced; at the same time, the temperature is accurately controlled, so that the furnace temperature is always lower than 1730 ℃, and the chromium oxidation is reduced. In the pre-reduction period, ferrosilicon alloy is used as a deoxidizer and alloying agent for deoxidation, due to the reasonable process parameter setting and implementation in the decarburization process, the chromium burning loss and oxidation are obviously reduced, the amount of ferrosilicon alloy for alloy element reduction is also obviously reduced, and slag supplement is carried out during the period. The silicon reduction alloy element and slag supplement are both exothermic reactions, reducing the amount of ferrosilicon alloy can reduce heat, and reducing the amount of cooling agent added to avoid overheating of the furnace temperature, which not only prevents the furnace lining from being severely eroded, but more importantly, it can fully play the role of the reducing agent, so that the chromium-rich slag reduction has better thermodynamic conditions.
[0019] The present application can also meet the smelting of AOD-L furnace, when oxygen blowing and heating, the side oxygen blowing and the top oxygen blowing are combined, and the distance between the top oxygen lance and the metal liquid surface is adjusted timely according to different oxygen blowing stages, so that the AOD furnace is heated faster, the oxidation time of chromium is reduced, and the slag has good fluidity; the temperature is kept above 1660 DEG C, and the high furnace temperature is beneficial to improve the decarburization efficiency and reduce the amount of reducing agent; the mass fraction ratio of CaO / SiO2 in the slag is controlled, the high alkalinity slag is beneficial to desulfurization, and the amount of aluminum used in the subsequent reduction process is also reduced; the reduction reaction of MgO in the refractory bricks of the furnace lining by SiO2 acidic slag at high temperature is also reduced, the loss of the AOD furnace lining is reduced, and the service life of the AOD furnace is improved.
[0020] As a preferred embodiment of the above technical solution, in step 2), the mass fraction ratio of CaO / SiO2 in the slag is controlled to be greater than or equal to 1.8.
[0021] As a preferred embodiment of the above technical solution, in step 2), the oxygen blowing decarburization includes three stages, the oxygen-to-argon ratio or the oxygen-to-nitrogen ratio is 4:1 in the first stage, the carbon content is reduced to below 0.5%; in the second stage, the oxygen-to-argon ratio or the oxygen-to-nitrogen ratio is gradually reduced to 5:2, and then to 2:1, and the carbon content is reduced to 0.1±0.02%; in the third stage, the oxygen-to-argon ratio or the oxygen-to-nitrogen ratio is reduced to 1:3, and then to 1:4, and when the carbon content is reduced to ≤0.018%, the reduction stage is entered.
[0022] As a preferred embodiment of the above technical solution, in the first stage of the oxygen blowing decarburization process, at least one of ferroalloy and return material of the same steel grade is added as a coolant to ensure that the temperature of the molten pool is between 1665 DEG C and 1675 DEG C; in the second stage of the oxygen blowing decarburization process, return material of the steel being smelted is added as a coolant to ensure that the maximum temperature of the molten pool does not exceed 1685 DEG C; in the third stage of the oxygen blowing decarburization process, return material of the steel being smelted is added as a coolant to ensure that the maximum temperature of the molten pool does not exceed 1730 DEG C.
[0023] As a preferred embodiment of the above technical solution, in step 2), the oxygen blowing flow rate is controlled to be 0.5-0.8 m^3 / (m*t), and the oxygen blowing pressure is controlled to be 1.0-1.1 Mpa.
[0024] As a preferred embodiment of the above technical solution, the slag-making agent in the batching and oxygen blowing decarburization step is lime, and the addition amount is 28-38 kg / t; the slag-making agent in the pre-reduction step is lime and fluorite, wherein the lime is 12-20 kg / t, and the fluorite is 8-18 kg / t; the slag-making agent in the tapping step is lime and fluorite, wherein the lime is 22-32 kg / t, and the fluorite is 8-18 kg / t.
[0025] As a preferred embodiment of the above technical solution, the temperature of the molten steel in the tapping step is always kept below 1730 DEG C.
[0026] As the preferred technical solution of the above-mentioned technical scheme, the chemical composition of the austenitic stainless steel is as follows: Cr 13-19.5wt%, Ni 13-22wt%, Si 4.5-6.5wt%, Cu 0.30-1.5wt%, Mo 0.75-2.5wt%, N≤0.10wt%, C≤0.07wt%, Mn≤2wt%, S≤0.015wt%, P≤0.03wt%, Al≤0.3wt%, and inevitable impurities, and the balance is Fe.
[0027] The present application is a kind of austenitic stainless steel resistant to high temperature and high concentration sulfuric acid;After comparison, the steel grade of the prior art, foreign company develops Zecor, Saramet35, sandvik SX and the steel grade of the present application are similar in material design and comprehensive performance, compared with foreign steel grade, the present application steel grade has more obvious advantages in material manufacturing process, yield improvement, corrosion resistance and the like;Sulfuric acid production process is relatively complex, temperature and concentration change frequently, the formula of the present application steel can be optimized in depth according to the actual working condition, so that more ideal effect is obtained: for higher temperature and higher concentration of equipment parts, Cr and Ni content is selected as upper limit, and for normal high temperature and normal concentration of equipment parts, Cr and Ni content is selected as lower limit.
[0028] In the formation process of stainless steel, two opposite forces act simultaneously: ferrite elements continuously form ferrite, and austenite elements continuously form austenite. The final crystal structure depends on the relative amount of the two types of added elements. In the above technical scheme of the present application, the following factors are mainly considered in the composition design:
[0029] Chromium: is a ferrite forming element, chromium and oxygen can form corrosion-resistant chromium trioxide, which is one of the basic elements to maintain corrosion resistance. Reasonable proportion of chromium and nickel can not only ensure the oxidation corrosion resistance of stainless steel, but also ensure high temperature strength, which is the basic element of austenitic heat-resistant stainless steel. At the same time, chromium can also form carbide or carbonitride with C and N elements, which can be precipitated in the crystal to play the role of second phase strengthening, and can also be precipitated in the grain boundary to play the role of pinning grain boundary, so that the material obtains good strength.
[0030] Nickel: the main role of nickel in stainless steel is to change the crystal structure of steel, form austenitic crystal structure, and improve plasticity, toughness and the like. The crystal structure of ordinary carbon steel is called ferrite, which is body-centered cubic (BCC) structure. By adding nickel, the crystal structure is changed from body-centered cubic (BCC) structure to face-centered cubic (FCC) structure, which is called austenite. Therefore, nickel is an important element to ensure the formation of austenite.
[0031] Carbon: strong austenite forming element, can form MX phase Nb(C, N) type precipitate strengthening, both can improve the strength of steel, but also can stabilize austenite structure, but has adverse effects on corrosion resistance. Therefore, the carbon content needs to be controlled within a certain range, and the lower limit of the material of the present application is considered.
[0032] Silicon: can improve the chloride stress corrosion cracking resistance, pitting and crevice corrosion resistance and seawater corrosion resistance of stainless steel; can improve the corrosion resistance of stainless steel in strong oxidizing medium (such as nitric acid, high temperature concentrated sulfuric acid), and can improve the high temperature oxidation resistance of stainless steel; silicon is also one of the cheap and easy to obtain alloying elements. But too high silicon content will promote the formation of brittle σ phase or silicon-rich G phase precipitates at grain boundaries. The present application uses silicon element which is cheap and easy to obtain. The addition of silicon promotes the passivation of stainless steel and forms a passivation film with SiO2 as the outer layer and Cr2O3 as the inner layer. The acid resistance of stainless steel is significantly improved. More importantly, the silicon element is divided into two sections: low content of 4.5-6.0% and high content of 5.5-6.5%, so as to meet the production process of sulfuric acid with different concentration intervals, different temperatures and different flow rates. The present application also gives a reasonable way of adding silicon element (adding 10-15 kg / t silicon-iron alloy for pre-reduction), which can not only ensure that the silicon element composition meets our expected target, but also prevent the erosion of the refining furnace lining caused by the formation of acid slag in silicon-containing steel.
[0033] Copper: has a certain effect on cold working and corrosion resistance, and is a very important element for forming nano Cu-rich phase precipitate strengthening in high-temperature chromium-nickel austenitic steel. Due to the uniform precipitation strengthening of a large number of Cu-rich phases, excellent strengthening effect is achieved.
[0034] Molybdenum: strong carbide forming element, the formed carbide is extremely stable, can prevent grain growth of austenite during heating, reduce the overheating sensitivity of steel, and molybdenum element can make the passivation film more dense and firm, thereby effectively improving the corrosion resistance of stainless steel.
[0035] Manganese: manganese is a weak austenite forming element, but has a strong effect on stabilizing austenite. Studies have shown that in nickel-chromium stainless steel, as the manganese content increases, the strength of the stainless steel increases. Manganese has strong affinity for sulfur in nickel-chromium stainless steel, which is beneficial to eliminate the harmful effect of sulfur. However, further studies have shown that the formation of manganese sulfide in stainless steel leads to a decrease in chloride pitting corrosion and crevice corrosion resistance. Therefore, the content of manganese needs to be controlled. In chromium-nickel stainless steel, the manganese content is generally not more than 2wt%, and the present application requires that the manganese content be reduced to less than 1.5wt%, and the actual control is about 1.0wt%.
[0036] Sulfur: Sulfur is a harmful impurity element in stainless steel, which mainly reduces the hot plasticity of austenitic stainless steel, affects the hot workability, and reduces the corrosion resistance, especially the hot plasticity. Because sulfur is segregated at the grain boundary, the grain boundary bonding force is reduced, resulting in a decrease in high temperature stress rupture strength. Generally, the sulfur content in nickel-chromium stainless steel is usually controlled below 0.03wt%. The present application requires that the sulfur content be controlled below 0.015wt%, and the actual control is below 0.005wt%.
[0037] Phosphorus: Phosphorus is a harmful impurity element in stainless steel, which can cause certain brittleness in austenitic stainless steel when it is too high. Generally, the sulfur content in nickel-chromium stainless steel is usually controlled below 0.035wt%. The present application requires that the sulfur content be controlled below 0.030wt%, and the actual control is below 0.025wt%.
[0038] As a preferred embodiment of the above technical solution, in the austenitic stainless steel, C≤0.02wt%, N≤0.025wt%.
[0039] As a preferred embodiment of the above technical solution, in the austenitic stainless steel, Mn≤1.5wt%, Al≤0.1wt%.
[0040] As a preferred embodiment of the above technical solution, the austenitic stainless steel further comprises the following components: B
[0041] 0.001-0.008wt%.
[0042] Boron: Boron is a trace element that is beneficial to strengthening the grain boundary. Boron segregation at the grain boundary can control the morphology of M 23 C6 carbide on one hand, and boron can strengthen the grain boundary and increase the stress rupture strength of the steel on the other hand. However, excessive boron can produce too much boride eutectic, which can weaken the grain boundary bonding force. The present application adds an appropriate amount of boron element to strengthen the grain boundary and improve the comprehensive mechanical properties of the material.
[0043] As a preferred embodiment of the above technical solution, the austenitic stainless steel further comprises rare earth elements, and the content of rare earth elements is 0.01-0.080wt%.
[0044] Rare earth elements: have obvious deoxidizing and desulfurizing effect, with the increase of rare earth elements in the steel, the oxygen and sulfur content is reduced, and trace rare earth elements have the effect of strengthening the grain boundary and improving the high temperature hot plasticity of the steel.
[0045] As a preferred embodiment of the above technical solution, the unavoidable impurities include: S<0.005wt%, P<0.030wt%, Bi<0.025wt%, As<0.025wt%, Pb<0.025wt%, Sn<0.025wt%, Sb<0.025wt%.
[0046] Lead Pb: low melting point substance, harmful element, reduce as much as possible.
[0047] Tin Sn: low melting point substance, harmful element, reduce as much as possible.
[0048] Arsenic As: low melting point substance, harmful element, reduce as much as possible.
[0049] Antimony Sb: low melting point substance, harmful element, reduce as much as possible.
[0050] Bismuth Bi: low melting point substance, harmful element, reduce as much as possible.
[0051] As a further preferred embodiment of the above technical solution, the sum of Bi, As, Pb, Sn, Sb is <0.05wt%.
[0052] As a further preferred embodiment of the above technical solution, the composition of the austenitic stainless steel is: Cr 13-15wt%, Ni 13-17wt%, Si 5.0-6.5wt%, Cu 0.75-1.5wt%, Mo 0.75-1.5wt%, C≤0.02wt%, Mn≤1.5wt%, S≤0.005wt%, P≤0.03wt%, Al≤0.1wt%, N≤0.025wt%, B 0.001-0.006wt%, rare earth 0.01-0.06wt%, Bi<0.020wt%, As<0.020wt%, Pb<0.020wt%, Sn<0.020wt%, Sb<0.020wt%, the balance being Fe.
[0053] As another preferred embodiment of the above technical solution, the composition of the austenitic stainless steel is: Cr 13-14wt%, Ni 15-17wt%, Si 5.5-6.5wt%, Cu 0.8-1.2wt%, Mo 0.8-1.2wt%, C≤0.02wt%, Mn≤1.5wt%, S≤0.005wt%, P≤0.03wt%, Al≤0.1wt%, N≤0.025wt%, B 0.001-0.006wt%, rare earth 0.01-0.06wt%, Bi<0.020wt%, As<0.020wt%, Pb<0.020wt%, Sn<0.020wt%, Sb<0.020wt%, the balance being Fe.
[0054] As another preferred of the above technical solution, the austenitic stainless steel is composed of: Cr 16.5-19.5wt%, Ni 19-22wt%, Si 4.5-6.0wt%, Cu 0.30-1.5wt%, Mo 1.5-2.5wt%, C≤0.02wt%, Mn≤1.5wt%, S≤0.005wt%, P≤0.03wt%, Al≤0.1wt%, N≤0.025wt%, B 0.001-0.006wt%, rare earth 0.01-0.06wt% Bi<0.020wt%, As<0.020wt%, Pb<0.020wt%, Sn<0.020wt%, Sb<0.020wt%, and the balance of Fe.
[0055] 0.020wt%, Sn<0.020wt%, Sb<0.020wt%, and the balance of Fe.
[0056] As another preferred of the above technical solution, the austenitic stainless steel is composed of: Cr 16.5-19.5wt%, Ni 19-22wt%, Si 4.5-6.0wt%, Cu 0.30-1.5wt%, Mo 1.5-2.5wt%, C≤0.02wt%, Mn≤1.5wt%, S≤0.005wt%, P≤0.03wt%, Al≤0.1wt%, N≤0.025wt%, B 0.001-0.006wt%, rare earth 0.01-0.06wt% Bi<0.020wt%, As<0.020wt%, Pb<0.020wt%, Sn<0.020wt%, Sb<0.020wt%, and the balance of Fe.
[0057] In summary, the present application has the following beneficial effects:
[0058] 1. The present application adopts the process flow of electric arc furnace-AOD / VOD-LF, specifically, in the decarburization process, the balance relationship of chromium-carbon-temperature in stainless steel smelting is fully considered, the oxygen blowing parameters are accurately controlled, the reasonable oxygen-argon ratio or oxygen-nitrogen ratio control is matched, the rapid temperature rising and high temperature maintaining of the duration are ensured, the carbon is preferentially oxidized, the oxygen supply intensity is improved, the oxygen blowing time is obviously shortened, the chromium burning loss is reduced, the end point carbon content is reduced, and the temperature is accurately controlled, so that the furnace temperature is always lower than 1730 DEG C, and the chromium oxidation is reduced.
[0059] 2. During the pre-reduction period, ferrosilicon alloy is used as a deoxidizer and alloying agent for deoxidation. Due to the reasonable process parameter settings and implementation in the decarburization process, the burn-off and oxidation of chromium are significantly reduced, and the amount of ferrosilicon alloy used for alloying element reduction is also significantly reduced. During this period, slag replenishment is required. Both silicon reduction alloying element and slag replenishment are exothermic reactions. Reducing the amount of ferrosilicon alloy can reduce heat and reduce the amount of coolant added to avoid furnace overheating. This not only prevents severe corrosion of the furnace lining, but more importantly, it can give full play to the role of the reducing agent and make the reduction of chromium-rich slag have better thermodynamic conditions.
[0060] 3. This invention can simultaneously meet the smelting requirements of AOD-L furnaces. During oxygen blowing and heating, a combination of side and top oxygen blowing is used, and the distance between the top oxygen lance and the molten metal surface is adjusted in a timely manner according to different stages of oxygen blowing, so that the AOD furnace heats up faster, reduces the oxidation time of chromium, and maintains good slag fluidity. Maintaining the temperature above 1660℃ and keeping the furnace temperature at a higher level is beneficial to improving decarburization efficiency and reducing the amount of reducing agent used. In addition, the mass fraction ratio of CaO / SiO2 in the slag is controlled, and the high basicity of the slag is beneficial to desulfurization, which also reduces the amount of metallic aluminum used in subsequent reduction processes. It also reduces the reduction reaction of SiO2 acidic slag on MgO in the furnace lining refractory bricks at high temperatures, reduces the wear of the AOD furnace lining, and increases the service life of the AOD furnace.
[0061] 4. This invention is an austenitic stainless steel resistant to high-temperature and high-concentration sulfuric acid. Through comparison, among existing steel grades, those developed by foreign companies such as Zecor, Saramet35, and Sandvik SX are similar to the steel grade of this invention in terms of material design and overall performance. Compared to foreign steel grades, the steel grade of this invention has more significant advantages in material manufacturing processes, yield improvement, and corrosion resistance. Since sulfuric acid production processes are complex, with frequent changes in temperature and concentration, the formulation of the steel grade of this invention can be deeply optimized according to actual working conditions to achieve more ideal results: for equipment components used at higher temperatures and higher concentrations, the Cr and Ni content should be at the upper limit; for equipment components used at normal high temperatures and normal concentrations, the Cr and Ni content should be at the middle to lower limit.
[0062] 5. This invention uses silicon, which is inexpensive and readily available. The addition of silicon promotes the passivation of stainless steel and forms a passivation film on its surface, with an outer layer mainly composed of SiO2 and an inner layer mainly composed of Cr2O3. This significantly improves the acid resistance of stainless steel. More importantly, the silicon content is divided into two ranges: low to medium content (4.5-6.0%) and high content (5.5-6.5%), thus meeting the needs of sulfuric acid production processes with different concentration ranges, temperatures, and flow rates. This invention also provides a reasonable method for adding silicon, which can ensure that the silicon composition reaches our expected target while preventing the formation of acidic slag in silicon-containing steel, which can affect the life of the refining furnace lining.
[0063] 6、The application adds appropriate amount of boron element, strengthens the grain boundary, and improves the comprehensive mechanical properties of the material;
[0064] 7、The application also discloses a method for desulfurization by adding appropriate amount of rare earth element and using the strong affinity of the rare earth element to sulfur element, so as to reduce the plasticity reduction caused by the sulfur element;
[0065] 8、The application also makes clear provisions for the elements of sulfur, phosphorus, aluminum, lead, tin, arsenic, antimony, bismuth and the like;
[0066] 9、The super-large size high-temperature concentrated sulfuric acid resistant stainless steel of the application is very sensitive to heating temperature, but according to the preparation method of the application, the cracking and other quality problems caused by temperature can be effectively avoided. BRIEF DESCRIPTION OF DRAWINGS
[0067] Figure 1 is a metallographic phase diagram of the super-large size high-temperature concentrated sulfuric acid resistant austenitic stainless steel prepared by the embodiment 14 of the application;
[0068] Figure 2 is a metallographic phase diagram of the austenitic stainless steel prepared by the comparative example 1;
[0069] Figure 3 is a grain corrosion result diagram of the steel plate of the embodiment 14;
[0070] Figure 4 is a grain corrosion result diagram of the steel plate of the comparative example 1. DETAILED DESCRIPTION
[0071] The application will be further explained and described below with reference to the accompanying drawings.
[0072] The specific embodiment is only an explanation of the application, and is not a limitation of the application. Any change made by the person skilled in the art after reading the specification of the application will be protected by the patent law as long as the change is within the scope of the claims.
[0073] Embodiment 1
[0074] The formula of the super-large size high-temperature concentrated sulfuric acid resistant austenitic stainless steel of the embodiment is shown in Table 1
[0075] Table 1
[0076]
[0077] A preparation method of a super-large size high-temperature concentrated sulfuric acid resistant austenitic stainless steel, comprising the following steps:
[0078] 1) Material preparation: according to the chemical composition of austenitic stainless steel in Table 1 and the burning loss, raw materials are prepared, the raw materials are melted into molten steel, 30 kg / t of slagging agent is added for primary refining, the oxidized metal in the molten steel is reduced by a reducing agent, and the Cr content in the molten steel is adjusted to be higher than the lower limit of the target value specified for the steel grade; when the temperature of the molten steel reaches 1650℃, the molten steel is discharged;
[0079] 2) Oxygen blowing decarburization: the molten steel is poured into a vacuum decarburization refining furnace, first slag is pulled, then the alloy raw material to be added is calculated according to the composition of the poured steel, the temperature of the molten steel is maintained above 1600℃, then refining is performed, oxygen blowing decarburization is performed when the initial carbon content is 1.0%, 30 kg / t of slagging agent is added for slagging, and the temperature is controlled to reach 1730℃, when the carbon is lower than 0.018%, the next step is entered;
[0080] 3) Reduction: 15 kg / t of ferrosilicon alloy is added to the molten steel for pre-reduction, when the chromium oxide in the slag is completely reduced, all the pre-reduction slag is removed; metal silicon is added for alloying, so that the silicon element reaches the target value; the slagging agent is added again, 2.0 Kg / T of strong deoxidizing agent aluminum is added, and deep deoxidization and desulfurization are performed;
[0081] 4) Tapping: the molten steel after completing deoxidization is analyzed for chemical composition, and necessary alloying elements such as Ni, Cr, Mo are added for final composition fine tuning, argon is blown in for stirring, and when the temperature is 1620℃, the molten steel is tapped into an LF ladle;
[0082] 5) Ladle refining: the slag is polarized by electrodes and the temperature is raised, the temperature is adjusted to the casting temperature, argon is bottom blown, and the non-metallic inclusions in the molten steel are removed by using dispersed argon bubbles;
[0083] 6) Casting: the molten steel in the LF ladle is cast into an ingot by using the bottom pouring method, the ingot is slowly cooled and then demoulded, and the cooling speed is ≤100℃ / h; the ingot shape is a tapered square ingot, the large end of the ingot size is between 600-700mm, and the small end of the ingot size is between 500-600mm; in this embodiment, the large end of the ingot size is controlled to be 650mm, and the small end of the ingot size is controlled to be 550mm;
[0084] 7) Piercing: the ingot after surface treatment is pierced by forging equipment; the ingot heating temperature is 1180℃, and the finish rolling temperature is ensured to be above 950℃; the piercing is divided into three heats, the ingot is roughly reduced to 1350mm in the first heat, the slab is transversely expanded in the second heat, the thickness reaches 300mm, and the width reaches 1450mm, and the slab is longitudinally elongated in the third heat, so that the final slab size reaches width >1500mm, thickness >180mm, and length >2200mm;
[0085] 8) Hot rolling: first hot rolling, billet heating temperature 1180°C, finishing temperature ensured above 950°C; first hot rolling size width greater than 1550mm, thickness greater than 28mm; second hot rolling, billet heating temperature 1160°C, finishing temperature ensured above 960°C; second hot rolling size width greater than 1650mm, thickness between 6.0-12mm, length > 6500mm;
[0086] 9) Solution: solution temperature 1080°C, holding time 20min;
[0087] 10) Oxide removal: physical polishing, then pickling with mixed acid of nitric acid + hydrofluoric acid to remove surface black oxide;
[0088] 11) Inspection: PT liquid penetration inspection on the four sides of the plate (50mm from the edge), ensuring no defects.
[0089] Example 2
[0090] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this example is shown in Table 2
[0091] Table 2
[0092]
[0093] In this example, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0094] Example 3
[0095] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this example is shown in Table 3
[0096] Table 3
[0097]
[0098] In this example, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0099] Example 4
[0100] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this example is shown in Table 4
[0101] Table 4
[0102]
[0103] In this example, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0104] Example 5
[0105] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 5
[0106] Table 5
[0107]
[0108] In this embodiment, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that in Embodiment 1.
[0109] Embodiment 6
[0110] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 6
[0111] Table 6
[0112]
[0113] In this embodiment, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that in Embodiment 1.
[0114] Embodiment 7
[0115] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 7
[0116] Table 7
[0117]
[0118]
[0119] In this embodiment, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that in Embodiment 1.
[0120] Embodiment 8
[0121] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 8
[0122] Table 8
[0123]
[0124] In this embodiment, the preparation method of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that in Embodiment 1.
[0125] Embodiment 9
[0126] The formula of the super-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 9
[0127] Table 9
[0128]
[0129] In this embodiment, the preparation method of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0130] Example 10
[0131] The formula of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 10
[0132] Table 10
[0133]
[0134] In this embodiment, the preparation method of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0135] Example 11
[0136] The formula of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 11
[0137] Table 11
[0138]
[0139]
[0140] In this embodiment, the preparation method of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0141] Example 12
[0142] The formula of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 12
[0143] Table 12
[0144]
[0145] In this embodiment, the preparation method of the super-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0146] From the products of Examples 1-4, 5-8, and 9-12, longitudinal samples were taken on the plate, and the tensile strength and elongation at break were measured according to the standard ASTM A370. The results are as follows
[0147] Furnace No. Tensile strength (MPa) Elongation Example 1 539 47 Example 2 533 52 Example 3 536 57 Example 4 526 59 Example 5 629 45 Example 6 657 50 Example 7 672 65 Example 8 667 63 Example 9 678 43 Example 10 692 52 Example 11 708 59 Example 12 712 69
[0148] From the above three groups of data, it can be seen that the effect of Example 7 and Example 12 is better. In Example 7, the chromium content is 16wt%, and the nickel content is 18wt%; in Example 12, the chromium content is 19.5wt%, and the nickel content is 22wt%. It is indicated that the content of nickel and chromium needs to have a suitable ratio to maximize the effect of alloying elements on stainless steel. In Examples 1-5, the content of at least one element is low; in Examples 9-10, the nickel content is low relative to the chromium content, and therefore the elongation is insufficient.
[0149] Considering the comprehensive cost and the actual application effect, the optimal ratio of elements is further studied based on the data of Example 7 as the empirical data.
[0150] Example 13
[0151] The formula of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel in this example is shown in Table 13
[0152] Table 13
[0153]
[0154] In this example, the preparation method of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel is the same as that of Example 1.
[0155] Example 14
[0156] The formula of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel in this example is shown in Table 14
[0157] Table 14
[0158]
[0159] In this example, the preparation method of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel is the same as that of Example 1.
[0160] Example 15
[0161] The formula of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel in this example is shown in Table 15
[0162] Table 15
[0163]
[0164] In this example, the preparation method of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel is the same as that of Example 1.
[0165] Example 16
[0166] The formula of the super-thin thickness high-temperature concentrated sulfuric acid-resistant austenitic stainless steel in this example is shown in Table 16
[0167] Table 16
[0168]
[0169] In this embodiment, the preparation method of the ultra-thin thickness high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0170] Example 17
[0171] The formula of the ultra-thin thickness high-temperature resistant concentrated sulfuric acid austenitic stainless steel in this embodiment is shown in Table 17
[0172] Table 17
[0173]
[0174] In this embodiment, the preparation method of the ultra-thin thickness high-temperature resistant concentrated sulfuric acid austenitic stainless steel is the same as that of Example 1.
[0175] Comparative Example 1
[0176] In this comparative example, commercially available heat-resistant stainless steel with trade name S32615 is used. The chemical composition of the steel is shown in Table 18.
[0177] Table 18
[0178]
[0179] Figure 1 is the metallographic image of the ultra-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel prepared in Example 14; Figure 2 is the metallographic image of the austenitic stainless steel prepared in Comparative Example 1. From Figure 1 and 2 it can be seen that there are a large number of precipitates in the austenitic stainless steel prepared in Comparative Example 1, which may be due to the fact that the chemical composition and preparation process of the comparative example are not optimized. These precipitates can seriously affect the corrosion resistance and processing performance of the material. The ultra-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel prepared by the present application has no precipitates, stable structure, excellent corrosion resistance and processing performance.
[0180] The stainless steels of Example 14 and Comparative Example 1 were subjected to relevant performance tests.
[0181] 1. Intergranular corrosion test. Test method: ASTM A262 E method. Sensitization treatment: 675℃, 1h, air cooling. Test conditions: 16% sulfuric acid-6% copper sulfate solution + copper chips, micro-boiling, 15h and above. Bending angle 180°.
[0182] Results: As shown in Figure 3 , the intergranular corrosion result of the steel plate of Example 14 is qualified, and the plate does not crack after bending. As shown in Figure 4The results of the crystal corrosion of the steel plate of Comparative Example 1 were not qualified, and the plate cracked after bending.
[0183] 2. Tensile at room temperature. The samples were taken longitudinally on the plate, and the standard reference ASTM A370 was used for the test.
[0184] Furnace No. Yield strength (MPa) Tensile strength (MPa) Elongation (%) Contraction of section (%) Example 14 320 685 67.0 53.0 Comparative Example 1 460 819 17.5 19
[0185] As can be seen from the above table, the elongation and the reduction of area of Comparative Example 1 are far lower than those of Example 14, and the tensile strength and the yield strength are far higher than those of Example 14, which indicates that Comparative Example 1 contains a large amount of precipitated phase, and the plasticity is extremely poor.
Claims
1. A method for preparing an ultra-large-size high-temperature-resistant concentrated sulfuric acid austenitic stainless steel, comprising the following steps: 1) batching: according to the chemical composition of the austenitic stainless steel and the burn loss, raw materials are prepared, the raw materials are melted into molten steel, 28-35 kg / t of slag forming agent is added for primary refining, the oxidized metal in the molten steel is reduced by a reducing agent, and the Cr content in the molten steel is adjusted to be higher than the lower limit of the target value specified for the steel grade; when the temperature of the molten steel reaches 1625-1650 ℃, the molten steel is discharged; 2) oxygen blowing decarburization: the molten steel is poured into an argon-oxygen refining furnace or a vacuum decarburization refining furnace, slag is first drawn, then the alloy raw material to be added is calculated according to the composition of the poured steel, the temperature of the molten steel is maintained above 1600 ℃, then refining is performed, oxygen blowing decarburization is performed when the initial carbon content is 1.0±0.2%, 28-35 kg / t of slag forming agent is added for slagging, and the temperature is controlled to reach 1730 ℃, and when the carbon is lower than 0.018%, the next step is entered; 3) reduction: 10-15 kg / t of ferrosilicon alloy is added to the molten steel for pre-reduction, after the chromium oxide in the slag is completely reduced, all the pre-reduction slag is removed, and the silicon element reaches the target value; the slag forming agent is added again, 1.5-2.0 kg / t of strong deoxidizer aluminum is added, and deep deoxidization and desulfurization are performed; 4) steel tapping: the molten steel after completing deoxidization is analyzed for chemical composition, and necessary adjustment of the final composition of alloy elements such as Ni, Cr and Mo is made, argon is blown for stirring, and the molten steel is tapped into an LF ladle when the temperature is 1590-1630 ℃; 5) ladle refining: the slag is polarized by using an electrode, and the temperature is raised, the temperature is adjusted to the casting temperature, argon is bottom-blown, and the molten steel is weakly stirred to remove non-metallic inclusions in the molten steel by using dispersed argon bubbles; 6) casting: the molten steel in the LF ladle is cast into an ingot by using the bottom pouring method, the ingot is slowly cooled and then demolded, and the cooling speed is ≤100 ℃ / h; the ingot shape is a tapered square ingot, the large end of the ingot has a length of 600-700 mm, and the small end of the ingot has a length of 500-600 mm; 7) cogging: the ingot after surface treatment is cogged by a forging equipment; the ingot heating temperature is 1140-1200 ℃, and the final rolling or forging temperature is ensured to be above 950 ℃; the cogging is divided into three heats, the ingot is roughly forged to 1300-1400 mm in the first heat, the slab is transversely expanded in the second heat, the thickness reaches 300 mm, and the width reaches 1450 mm, and the slab is longitudinally elongated in the third heat, and the final slab size reaches width > 1500 mm, thickness > 180 mm, and length > 2200 mm; 8) hot rolling: in the first hot rolling, the slab heating temperature is 1150-1190 ℃, and the final rolling temperature is ensured to be above 950 ℃; the first hot rolling size is width > 1550 mm and thickness > 28 mm; in the second hot rolling, the slab heating temperature is 1150-1170 ℃, and the final rolling temperature is ensured to be above 960 ℃; the second hot rolling size is width > 1650 mm, thickness is between 6.0 and 12 mm, and length > 6500 mm; 9) solid solution: the solid solution temperature is 1060-1100 ℃, and the holding time is 15-20 min. The chemical composition of the austenitic stainless steel is as follows: Cr 13~19.5wt%, Ni 13~22wt%, Si 4.5~6.5wt%, Cu 0.30~1.5wt%, Mo 0.75~2.5wt%, N≤0.10wt%, C≤0.07wt%, Mn≤2wt%, S≤0.015wt%, P≤0.03wt%, Al≤0.3wt%, and inevitable impurities, with the balance being Fe.
2. The method of claim 1, wherein the ultra-large-sized high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is prepared by the following steps. In step 2), the CaO / SiO2 mass fraction ratio in the slag is greater than or equal to 1.8 by adding slagging agents.
3. The method of claim 1, wherein the ultra-large-sized high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is prepared by the following steps. In step 2), the oxygen blowing decarburization includes three stages, the oxygen-argon ratio or oxygen-nitrogen ratio is 4:1 in the first stage, and the carbon content is reduced to less than 0.5%; In the second stage, the oxygen-argon ratio or oxygen-nitrogen ratio is gradually reduced to 5:2, and then to 2:1, and the carbon content is reduced to 0.1±0.02%; in the third stage, the oxygen-argon ratio or oxygen-nitrogen ratio is reduced to 1:3, and then to 1:4, and when the carbon content is reduced to ≤0.018%, the reduction stage is entered.
4. The method of claim 3, wherein the ultra-large-sized high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is prepared by the following steps. In the first stage of the oxygen blowing decarburization process, at least one of ferroalloy and return material of the same steel grade is added as a coolant to ensure that the temperature of the molten pool is between 1665~1675℃; in the second stage of the oxygen blowing decarburization process, return material of the same steel grade is added as a coolant to ensure that the maximum temperature of the molten pool does not exceed 1685℃; in the third stage of the oxygen blowing decarburization process, return material of the same steel grade is added as a coolant to ensure that the maximum temperature of the molten pool does not exceed 1730℃.
5. The method of claim 3, wherein the ultra-large-sized high-temperature-resistant concentrated sulfuric acid austenitic stainless steel is prepared by the following steps: In step 2), the oxygen blowing flow rate is controlled at 0.5~0.8 m^3 / (m*t), and the oxygen blowing pressure is controlled at 1.0~1.1MPa. 6. The method of claim 1, wherein the ultra-large size high temperature resistant concentrated sulfuric acid austenitic stainless steel is prepared by the following steps. The slagging agent in the pre-reduction step is lime and fluorite, wherein the lime is 12~20kg / t, and the fluorite is 8~18kg / t; the slagging agent in the tapping step is lime and fluorite, wherein the lime is 22~32kg / t, and the fluorite is 8~18kg / t.
7. The method for preparing ultra-large-size high-temperature resistant concentrated sulfuric acid austenitic stainless steel according to claim 1, characterized in that: The temperature of the molten steel in the tapping step is always kept below 1730℃.
8. The method for preparing ultra-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel according to claim 1, characterized in that: In the austenitic stainless steel, C≤0.02wt%, N≤0.025wt%.
9. The method for preparing ultra-large size high-temperature resistant concentrated sulfuric acid austenitic stainless steel according to claim 1, characterized in that: In the austenitic stainless steel, Mn≤1.5wt%, Al≤0.1wt%.
Citation Information
Patent Citations
Preparation method of austenitic stainless steel resisting high-temperature and high-concentration sulfuric acid
CN108118237A